Poly-GP in cerebrospinal fluid linksC9orf72-associated dipeptide repeat expression to the asymptomatic phase of ALS/FTD - Lehmer, Carina; Oeckl, Patrick; Weishaupt, Jochen H.; Volk, Alexander E.; Diehl-Schmid, Janine; Schroeter, Matthias L.; Lauer, Martin; Kornhuber, Johannes; Levin, Johannes; Fassbender, Klaus; Landwehrmeyer, Bernhard; Schludi, Martin H.; et al. (Embo Molecular Medicine, 2017)
TheC9orf72GGGGCC repeat expansion is a major cause of amyotrophic lateral sclerosis and frontotemporal dementia (c9ALS/FTD). Non-conventional repeat translation results in five dipeptide repeat proteins (DPRs), but their clinical utility, overall significance, and temporal course in the pathogenesis of c9ALS/FTD are unclear, although animal models support a gain-of-function mechanism. Here, we established a poly-GP immunoassay from cerebrospinal fluid (CSF) to identify and characterizeC9orf72patients. Significant poly-GP levels were already detectable in asymptomaticC9orf72mutation carriers compared to healthy controls and patients with other neurodegenerative diseases. The poly-GP levels in asymptomatic carriers were similar to symptomatic c9ALS/FTD cases. Poly-GP levels were not correlated with disease onset, clinical scores, and CSF levels of neurofilaments as a marker for axonal damage. Poly-GP determination in CSF revealed aC9orf72mutation carrier in our cohort and may thus be used as a diagnostic marker in addition to genetic testing to screen patients. Presymptomatic expression of poly-GP and likely other DPR species may contribute to disease onset and thus represents an alluring therapeutic target.
EVALuna2:33559